Expression of dna methyltransferases (dnmts) at mrna level in ovine endometrium during estrus cycle and early pregnancy - Mustafa Hitit; Mehmet Kose (Eurasian Journal of Veterinary Sciences)
Aim: To elucidate mRNA expression of DNA methyltransferase enzyme genes (DNMT1, DNMT3A, and DNMT3B) in ovine endometrium whether they are modulated during the estrus cycle and early pregnancy. Materials and Methods: The endometrial samples including intercaruncular sites was obtained from a total of 24 ewes on days of 12 (P12, n = 4), 16 (P16, n = 4) and 22 (P22, n = 4) of pregnancy following mating and cyclic days of 12 (C12, n = 4), 16 (C16, n = 4) and 22 (C22, n = 4) of the estrous cycle. The relative mRNA level of DNMTs were evaluated through real-time quantitative RT-qPCR. Results: Abundances of DNMTs including DNMT1, DNMT3A, and DNMT3B were detected during the estrous cycle and early pregnancy in the ovine endometrium by this study. DNMT1 mRNA steady-state level was greater in P16 than in C16 whereas they did not change within the rest of the groups. The level of DNMT3A mRNA, during early pregnancy, had the highest expression levels on P12 compared to P22 and P16 (p<0.01). However, the level of DNMT3A mRNA was lower in P16 than in C16 (p<0.01) and had a similar decrease in P22 compared to C22 (p<0.01). DNMT3B mRNA level did not differ (p>0.01) during the estrus cycle and early pregnancy. Conclusion: DNA methylation related DNMTs may be required to control of gene expression in the ovine endometrium during the estrus cycle and early pregnancy.